PENDEKATAN SISTEMATIS DALAM PERENCANAAN DAN PENGEMBANGAN KARIER: TANTANGAN SERTA FAKTOR PENENTU - Dwi Lestari; Fajri Rahmadeli; Tiffany Deanidia; Yulia Dwi Wahyuni (PT. Jurnal Center Indonesia Publisher, 2025)
Effective career planning and development is essential in the context of today's competitive and dynamic job market. A systematic approach is crucial to helping individuals and organizations identify and achieve their career goals. This research aims to analyze the importance of a systematic approach in career planning and development, the challenges faced, and the determining factors for success that need to be considered. The method used in this research is literature study, which includes analysis of related literature and best practices in career development. The research results show that self-assessment, setting clear goals, developing skills, as well as mentorship and technology support play an important role in achieving career success. Apart from that, organizations must also play an active role in providing structured development programs to increase employee engagement. The conclusion of this research emphasizes the need for synergy between individuals and organizations in creating a mutually beneficial career development ecosystem.